Analisis Efektivitas Pelaksanaan Program Pengembangan Usaha Mikro Kecil Dan Menengah Pada Dinas Perindustrian Perdagangan Koperasi Dan Ukm Kab. Aceh Singkil - Dedek Harlianda (SOSEK : Jurnal Sosial dan Ekonomi, 2022)
The purpose of this research is to find out how the effectiveness of the micro, small and medium enterprise (MSMEs) program is in improving business capital services (MSMEs), developing the entrepreneurial spirit of the community and improving the services of accompanying staff for SMEs in the Department of Industry, Trade, Cooperatives and SMEs. The method used in this research is descriptive method with qualitative analysis. Overall data analysis was carried out by describing the results of the interviews and then discussing and drawing conclusions. From the research it was found that the services provided by the Office of Industry, Trade, Cooperatives and UKM of Aceh Singkil Regency were not maximized. It can be seen that the objectives of the effectiveness of the micro, small and medium enterprise (MSMEs) program regarding providing business capital easily, quickly and without cost have not been realized. fully. Regarding the targets of the Micro, Small and Medium Enterprises (MSMEs) program which is being carried out at the Office of Industry, Trade, Cooperatives and UKM of Aceh Singkil Regency, it is in accordance with the stages determined based on the instructions which are the basis for carrying out the work. If you look at the mechanism, it is the same as a business capital loan with the usual process, you have to go through the stages and procedures. However, regarding timeliness, the Aceh Singkil Regency Industry, Trade and Cooperative Office has not been able to provide maximum service.